UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN BINTARO (Cerbera manghas L.) TERHADAP HAMA PENGGEREK TONGKOL JAGUNG MANIS (Helicoverpa armigera Hubner) - Muslihat; Desita Salbiah (DINAMIKA PERTANIAN, 2020)
ABSTRACT The main pest that often attacks sweet corn crops is Helicoverpa armigera Hubner and causes damage. Pest control can be done using botanical insecticide bintaro plants (Cerbera manghas L.) The aim of this research was to get an effective concentration of bintaro leaf flour extract against of Helicoverpa armigera Hubner. The research was carried out experimentally at the Laboratory of Plant Pests, Agricultural Faculty, University of Riau, by using a completely randomized design (CRD) with four treatments and five replications. The treatments consisted of the several levels of concentration of bintaro leaf flour extract, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water and 100 g.l-1 water. The parameters observed were initial time of death (hours), lethal time 50 (hours), and total mortality (%). The results showed that bintaro leaf extract with a concentration of 80 g.l-1 water was an effective concentration to control H. armigera pests which could cause a total mortality of 82% with an initial death of 15,4 hours after application and lethal time 50 (LT50) 57,4 hours after application. Keywords: Helicoverpa armigera Hubner, Bintaro plants, Botanical insecticide